2019
DOI: 10.3390/nu11061210
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Following Mediterranean Diet Recommendations in the Real World in the Incidence of Gestational Diabetes Mellitus (GDM) and Adverse Maternal-Foetal Outcomes: A Prospective, Universal, Interventional Study with a Single Group. The St Carlos Study

Abstract: We reported that a Mediterranean Diet (MedDiet), supplemented with extra-virgin olive oil (EVOO) and pistachios, reduces GDM incidence and several other adverse outcomes. In order to assess its translational effects in the real world we evaluated the effect of MedDiet from 1st gestational visit in GDM rate compared with control (CG) and intervention (IG) groups from the previously referred trial. As secondary objective we also compared adverse perinatal outcomes between normoglycemic and diabetic women. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
3
52
0
1
Order By: Relevance
“…Associations between the adherence to a MedDiet rich in extra virgin olive oil and nuts in pregnancy and improved materno-fetal events have been shown in women with and without GDM [7,8,9,12,13]. Results from these studies seem to indicate the benefits extend to the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Associations between the adherence to a MedDiet rich in extra virgin olive oil and nuts in pregnancy and improved materno-fetal events have been shown in women with and without GDM [7,8,9,12,13]. Results from these studies seem to indicate the benefits extend to the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of women used in this cohort study was retrieved mainly from three different studies [7,13,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature suggests that a Mediterranean style diet high in MUFA and PUFA reduced the incidence of GDM and infants that were LGA. 48 The efficacy of these fatty acids for dietary intervention and the use of maternal AL index as an indicator of intervention effectiveness during GDM deserve further investigation. A few micronutrients were supplemented to GDM women in previous studies but the intervention outcomes for the mother and child dyad showed mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review [4] found that compliance to a Mediterranean-style diet, categorized as one with relatively higher bread, cereal, legume, vegetable, fruit, fish and olive oil intakes and lower or limited animal fat, meat and egg intakes [5], led to a reduction in GDM risk of between 15–38%. Similarly, a trial where the intervention group ate a Mediterranean diet supplemented with olive oil and pistachio nuts led to a relative risk for GDM of 73% of that of a control group fed a standard diet [6] and a similar effect in a follow-up real world (non-trial) situation [7]. Consumption of this diet was also associated with a reduced risk of other adverse effects of pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%